Association of sunbed use with skin cancer risk factors in Europe: an investigation within the Euromelanoma skin cancer prevention campaign. (27th February 2019) - Suppa, M.; Gandini, S.; Njimi, H.; Bulliard, J.L.; Correia, O.; Duarte, A.F.; Peris, K.; Stratigos, A.J.; Nagore, E.; Longo, M.I.; Bylaite‐Bucinskiene, M.; Karls, R.; et al.
Abstract: Introduction: Sunbed use has been significantly associated with increased risk of melanoma and non‐melanoma skin cancer (NMSC), but its relationship with melanoma's risk factors such as high nevus count, atypical nevi and lentigines is poorly studied. Euromelanoma is a skin cancer prevention campaign conducted all over Europe. It offers a once‐a‐year screening during which participants' data, including sunbed use and phenotype, are collected via questionnaires. Objectives: To investigate the association of sunbed use with nevus count, atypical nevi, lentigines and suspicion of skin cancer. Methods: To ensure reliability of the data, we defined inclusion and exclusion criteria for countries' eligibility for the risk analysis. Multivariate logistic regression models (including age, gender, education, skin type, family history of melanoma, personal history of skin cancer, any sun exposure and any sunscreen use) were used to calculate summary odds ratios (SORs) of each clinical endpoint for ever sunbed use. Results: Overall, 227 888 individuals from 30 countries completed the Euromelanoma questionnaire. After the data quality check, 16 countries were eligible for the multivariate analysis, for a total of 145 980 participants (64.8% females; median age 43 years; 62.3% highly educated; 28.5% skin type I–II; 11.0% ever sunbed use). Ever sunbed use was independently associated with nevus count >50 [SOR = 1.05 (1.01–1.10)], atypical nevi [SOR = 1.04 (1.00–1.09)], lentigines [SOR = 1.16 (1.04–1.29)] and suspicion of melanoma [SOR = 1.13 (1.00–1.27)]. Conversely, no significant association was found between ever sunbed use and suspicion of NMSC [SOR = 1.00 (0.91–1.10)]. Conclusions: Indoor tanning is significantly associated with well‐recognized risk factors for melanoma (including high nevus count, presence of atypical nevi and lentigines) as well as suspicion of melanoma within the Euromelanoma screenees. In order to reduce the prevalence of melanoma risk factors, avoidance/discontinuation of sunbed use should always be encouraged, especially but not exclusively for individuals with high‐risk phenotypes.